Implementasi Putusan MK No. 46/PUU-VIII/2010 Terhadap Anak Hasil Nikah Siri - Abdul Aziz (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2017)
If religion has been declared invalid, the state inevitably must claim legitimate. Definition validity of a marriage is different from the standpoint of religion and state. In religion, the marriage is deemed valid if the conditions are met in harmony and. Meanwhile, legitimate according to the state, if the marriage is recorded in state documents. The state is still mind admitting children from unregistered marriages to hold the status of legitimate child. Quite often the child of unregistered marriages is referred to as a child out of wedlock. They still trouble in handling legal rights, such as income, inheritance, not even a birth certificate. Not only in the eyes of the law, in the social order, children are stamped out of wedlock have inférieur notch lower and worse than legitimate children. Legitimate son, in principle, under the authority of parents. Meanwhile, stamped unauthorized certainly be under guardianship. It also continues the legacy and the rights of other children. In the practice of everyday life, children born to legally married siri state still viewed not have a legal relationship with her father. Exactly the same law with a child out of wedlock. The birth certificate for example, are still encountered cases of child's birth certificate from unregistered marriages that did not include the name of the father. It is true, as stipulated in Article 55 paragraph 2 letter A Government Regulation No. 37 Year 2007 on the Implementation of the Law No. 23 Year 2006 concerning Population Administration.